Method of modifying a surface of a nozzle of a liquid dispenser used for manufacturing a liquid crystal display - LIM YONG WOON (2013)
A method of modifying a surface of the nozzle of a liquid dispenser used to dispense liquid for manufacturing a liquid crystal display (LCD) includes primarily modifying the surface of the nozzle by performing one of oxygen (O2) or ozone (O3) plasma treatment with respect to the surface of the nozzle, secondarily modifying the primarily modified surface of the nozzle by treating the primarily modified surface with aminopropyltriethoxysilane, and tertiary modifying the secondarily modified surface of the nozzle by allowing an epoxy resin to react with the secondarily modified surface of the nozzle.